2020
DOI: 10.1002/jcla.23360
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA CRNDE and toll‐like receptor 3 correlate with disease severity, inflammation, and mortality in sepsis

Abstract: Objective This study aimed to assess the interaction between long non‐coding RNA colorectal neoplasia differentially expressed (lncRNA CRNDE) and toll‐like receptor 3 (TLR3), and assess their correlations with disease severity, inflammation, and 28‐days mortality in sepsis patients. Methods We consecutively enrolled 146 sepsis patients and 146 healthy controls (HCs), and collected their peripheral blood mononuclear cells to detect lncRNA CRNDE and TLR3 expressions using reverse transcription quantitative polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…CRANDE plays a role in tumor proliferation, migration, and the occurrence of many other diseases ( Zhou et al, 2019a ; Xie et al, 2020 ). CRANDE interacts with TLR3, and both correlate with advanced disease inflammation in sepsis patients ( Yang et al, 2020 ). The other lncRNA, OIP5-AS1, has been reported to contribute to the progression of the atherosclerosis NF-κB pathway ( Ren et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…CRANDE plays a role in tumor proliferation, migration, and the occurrence of many other diseases ( Zhou et al, 2019a ; Xie et al, 2020 ). CRANDE interacts with TLR3, and both correlate with advanced disease inflammation in sepsis patients ( Yang et al, 2020 ). The other lncRNA, OIP5-AS1, has been reported to contribute to the progression of the atherosclerosis NF-κB pathway ( Ren et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some research has showed that lncRNAs modulated sepsis by regulating different signaling pathways, such as Toll-like receptor (TLR) signaling pathway ( 34 ), which activated nuclear factor κB (NF-κB), thereby triggered inflammatory response in sepsis. A Previous study has suggested that lncRNA hox transcript antisense RNA (HOTAIR) activated the NF-κB signaling pathway to promote TNF-α expression in a murine septic model ( 35 ).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%
“…A Previous study has suggested that lncRNA hox transcript antisense RNA (HOTAIR) activated the NF-κB signaling pathway to promote TNF-α expression in a murine septic model ( 35 ). Likewise, CRNDE and NEAT1 promoted the progression of sepsis-induced injury by regulating the NF-κB signaling ( 34 , 36 ).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%
“…The lnc-MALAT1/miR-125a axis presents excellent value in differentiating sepsis patients from healthy controls using peripheral blood samples ( 73 ). In another study using clinical blood samples, lnc-CRNDE was found to trigger inflammation through the TLR3-NF-κB-cytokine signaling pathway and the downstream release of inflammatory cytokines ( 74 ). As a major protein related to innate immune and inflammatory responses, TLR3 is known to cause cardiac dysfunction and other organ damage during sepsis ( 74 , 75 ).…”
Section: Lncrna Involved In Sicd Among Various Cell Typesmentioning
confidence: 99%
“…In another study using clinical blood samples, lnc-CRNDE was found to trigger inflammation through the TLR3-NF-κB-cytokine signaling pathway and the downstream release of inflammatory cytokines ( 74 ). As a major protein related to innate immune and inflammatory responses, TLR3 is known to cause cardiac dysfunction and other organ damage during sepsis ( 74 , 75 ). Low expression of lnc-MEG3 might also serve as a potential biomarker for the development, progression, and prognosis prediction of sepsis ( 76 78 ).…”
Section: Lncrna Involved In Sicd Among Various Cell Typesmentioning
confidence: 99%